Analisis Likuiditas PT Kalbe Farma Tbk Berdasarkan Laporan Keuangan - Rully Movizar; Eka Ayu Marella (Soratekno Publisher, 2025)
This study aims to determine the liquidity level of PT Kalbe Farma Tbk for the 2022–2024 period using cash flow ratio analysis, namely the Operating Cash Flow to Current Liabilities (OCL) Ratio, Cash Flow to Interest Ratio (CFL), Cash Flow to Total Debt Ratio (TLC), and Cash Flow to Net Income Ratio (NTR). The data used is secondary quantitative data obtained from the company's financial statements. The results show that the OSL ratio increased from 0.29 to 1.14, indicating an improvement in the company's ability to meet short-term obligations. The TLC ratio has been in excellent condition for three consecutive years. The TH ratio shows a positive trend and is approaching the ideal limit, while the ILC ratio increased from 0.37 to 1.47, reflecting improving earnings quality. Overall, PT Kalbe Farma Tbk's liquidity has improved significantly during the study period.